Enhancement LVRT capability of DFIG driven wind conversion system - Laafou, Abdeslam Jabal; Madi, Abdessalam Ait; Moumani, Youssef; Essakhi, Hassan (Institute of Advanced Engineering and Science, 2025)
In this paper we present two techniques for protecting the doubly fed induction generator (DFIG) in the event of external disturbances on the electrical network, the crowbar circuit and series dynamic braking resistor (SDBR) techniques. During voltage dips, the first technique is triggered and short-circuits the rotor side converter (RSC) so as to maintain the rotor current within the desired limits. As a result, the DFIG behaves as an asynchronous cage generator that absorbs the reactive power coming from the voltage dip on the network which does not meet the grid code's (GC) requirements. The second technique makes it possible to limit overcurrent’s at the level of the stator and rotor of the DFIG, it will enable the wind power system to continue operating normally once the fault has disappeared and to stay connected to the network throughout the voltage dip. This SDBR technique presents a good compromise between its performance, its simplicity, its efficiency, and its implementation’s cost.